BDNF VAL66MET polymorphism and memory decline across the spectrum of Alzheimer's disease. (6th January 2021) - Lim, Yen Ying; Laws, Simon M.; Perin, Stephanie; Pietrzak, Robert H.; Fowler, Christopher; Masters, Colin L.; Maruff, Paul
Abstract: The brain‐derived neurotrophic factor ( BDNF ) Val66Met (rs6265) polymorphism has been shown to moderate the extent to which memory decline manifests in preclinical Alzheimer's disease (AD). To date, no study has examined the relationship between BDNF and memory in individuals across biologically confirmed AD clinical stages (i.e., Aβ+). We aimed to understand the effect of BDNF on episodic memory decline and clinical disease progression over 126 months in individuals with preclinical, prodromal and clinical AD. Participants enrolled in the Australian Imaging, Biomarkers and Lifestyle (AIBL) study who were Aβ + (according to positron emission tomography), and cognitively normal (CN; n = 238), classified as having mild cognitive impairment (MCI; n = 80), or AD (n = 66) were included in this study. Cognition was evaluated at 18 month intervals using an established episodic memory composite score over 126 months. We observed that in Aβ + CNs, Met66 was associated with greater memory decline with increasing age and were 1.5 times more likely to progress to MCI/AD over 126 months. In Aβ + MCIs, there was no effect of Met66 on memory decline or on disease progression to AD over 126 months. In Aβ + AD, Val66 homozygotes showed greater memory decline, while Met66 carriers performed at a constant and very impaired level. Our current results illustrate the importance of time and disease severity to clinicopathological models of the role of BDNF Val66Met in memory decline and AD clinical progression. Specifically, the effect of BDNF on memory decline is greatest in preclinical AD and reduces as AD clinical disease severity increases. Abstract : We aimed to understand the effect of BDNF on memory decline and clinical disease progression over 126‐months in preclinical, prodromal and clinical AD. In Aβ+ CNs, Met66 was associated with greater memory decline and were 1.5 times more likely to progress to MCI/AD over 126‐months. There was no effect of Met66 on memory decline or on disease progression in Aβ+ MCIs. In Aβ+ AD, Val66 homozygotes showed greater memory decline, while Met66 carriers performed at a constant and very impaired level. Our results illustrate the importance of time and disease severity to the role of BDNF Val66Met in memory decline and clinical progression. Relationships between BDNF and memory decline is greatest in preclinical AD and reduces with increasing disease severity